IMPLEMENTASI PINJAM PAKAI BARANG BUKTI DALAM PERKARA PIDANA BERDASARKAN PERATURAN KEPALA KEPOLISIAN NEGARA REPUBLIK INDONESIA NOMOR 10 TAHUN 2010 TENTANG TATA CARA PENGELOLAAN BARANG BUKTI DI KEPOLISIAN RESOR KOTA PEKANBARU - Josua Karsia; Mukhlis Mukhlis; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Currently, in the Regulation of the Head of the State Police of the Republic of Indonesia Number 8of 2014 concerning Amendments to the Regulation of theHead of the State Police of the Republic ofIndonesia Number 10 of 2010 concerning Procedures for Managing Evidence in the National Police ofthe Republic of Indonesia there is no provision in the Article which states the cost of borrowing evidence.However, in reality there are not a few pieces of evidence in criminal cases where if used, the user mustpay a number of guarantees to existing law enforcement. Meanwhile, based on the principle of legalitywhich is based on the rule of law and the rule of law, the ranks of law enforcement officers are notjustified. The purpose of this study is to find out the implementation and legal impact of borrowing andusing evidence in criminal cases based on the Regulation of the Head of the National Police of theRepublic of Indonesia Number 10 of 2010 concerning Procedures for Managing Evidence at thePekanbaru City Police.This research uses the type of empirical legal research or sociological legal research. The sample inthis study were the head of the Pekanbaru City Resort Police and investigators at the Pekanbaru Police.The analytical tool in this study is a qualitative method. This study found that there were things that wereless than optimal in reality on the ground, so it was necessary to anticipate them with maximum effort.This study concluded that the implementation of borrowing evidence in criminal cases according tothe National Police Regulation number 10 of 2010 was not in accordance with existing legal provisions.The borrowing of evidence was accepted by police investigators without any determination from the trial.In addition, the act of asking for security deposits to parties who want to borrow using criminal evidenceis not allowed because these actions are outside the applicable legal provisions. However, thisphenomenon is still often carried out by police investigators. Investigators should not do this by askingfor security deposits from parties who want to borrow or use them. The legal impact on the borrowing ofevidence in criminal cases based on the Regulation of the Chief of the National Police of the Republic ofIndonesia Number 10 of 2010 concerning Procedures for Evidence Management at the Pekanbaru CityResort Police With the action of asking for a security deposit by the investigator on the evidence thatwants to be loaned to the applicant, the author considers the actions committed by the investigator to beillegal levies because these actions are not expressly regulated in Perkapolri number 10 of 2010.Keywords: Borrowing - Evidence - Criminal Case